Physical Stability, Photostability, and Sunscreen Effectiveness of Combination Cream of Arabica Green Coffee Bean Extract (Coffea arabica) and Octyl Methoxycinnamate - Nanda Tsalasani Zulfaidah; Endang Lukitaningsih; Abdul Karim Zulkarnain (Majalah Obat Tradisional, 2023)
Arabica green coffee beans (AGCB) have antioxidant compounds as photo protectors. It’s used to stabilize and increase the SPF value of octyl methoxycinnamate in sunscreen because its effectiveness will be decreased when exposed to UV light. The purpose of this study was to determine the effect of a combination of various concentrations of arabica green coffee bean (AGCB) extract and octyl methoxycinnamate (OMC) on the physical properties and SPF value of sunscreen cream. AGCB extract with concentrations (F1) 0%; (F2) 2.5%; (F3) 5%; (F4) 7.5% (with the addition of OMC concentration of 7.5%), and (F5) 7.5% (without the addition of OMC). The formulas were tested for physical properties to determine stability in 4 weeks of storage, cycling test for 4 cycles, and photostability to determine the SPF value and irritation test on the best formula. The results of the physical stability test on the five formulas showed a sig value > 0.05 which means the preparation is stable. Formulas F1, F2, F3, F4, and F5 with exposure of 1 hour, 5 hours, and 10 hours obtained a significance value > 0.05, which means that the presence of UV light exposure in the AGCB extract combination cream can stabilize the decrease in SPF value. Formula 4, which is stable without separation during the cycling test and the stability of the SPF value of 41, then in the irritation test does not cause irritation so it can be concluded that formula 4 is the optimum formula.